1991
DOI: 10.1080/00207599108247163
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Orientation in Children: Construction and Validation of the Child Altruism Inventory

Abstract: The Child Altruism Inventory (CAI) consisted of 24 yes‐or‐no items which measured the altruistic orientation of children. The sample included 1095 Grades 2 to 6 Chinese children in Hong Kong, The test‐retest and internal consistency reliabilities of the CAI were in the 0.70s. The correlations of the CAI score with the intelligence and self‐esteem scores were significantly positive, while the correlations of the CAI score with the psychoticism and neuroticism scores were significantly negative. Children in clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 24 publications
2
38
0
1
Order By: Relevance
“…The correlation of CEST with PB was, however, insignificant. The present findings are consistent with those in literature (Cheung, Ma, & Shek, 1998;Eisenberg & Fabes, 1998;Ma & Leung, 1991;Moos & Trickett, 1987). Results of correlation analysis provided partial support for the Hypothesis H3.…”
Section: Hypothesis Testingsupporting
confidence: 83%
See 3 more Smart Citations
“…The correlation of CEST with PB was, however, insignificant. The present findings are consistent with those in literature (Cheung, Ma, & Shek, 1998;Eisenberg & Fabes, 1998;Ma & Leung, 1991;Moos & Trickett, 1987). Results of correlation analysis provided partial support for the Hypothesis H3.…”
Section: Hypothesis Testingsupporting
confidence: 83%
“…In other words, it is important and essential for teachers to develop a prosocial orientation in their students starting when the students are quite young. Ma and Leung (1991) also found that a nice classroom social environment is positively associated with altruistic orientation.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, the rating of the DB or PB score is from 1.0 to 7.0. The reliability and validity of ABQ scores were demonstrated to be good in studies by Ma and Leung (1991) and Ma et al (1996). The reliability of the ABQ scores is usually in the .80s to .90s.…”
Section: Methodsmentioning
confidence: 99%